2019
DOI: 10.1016/j.csfx.2019.100004
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the clustering coefficient: A topological analysis of node neighbourhoods in complex networks

Abstract: In Network Science node neighbourhoods, also called ego-centered networks have attracted large attention. In particular the clustering coefficient has been extensively used to measure their local cohesiveness. In this paper, we show how, given two nodes with the same clustering coefficient, the topology of their neighbourhoods can be significantly different, which demonstrates the need to go beyond this simple characterization. We perform a large scale statistical analysis of the topology of node neighbourhood… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 38 publications
(60 reference statements)
0
47
0
Order By: Relevance
“…We inferred that acupuncture stimulation affected these functional connections. Moreover, we also found that acupuncture stimulation affected functional interaction (i.e., degree) (Cecilia et al, 2018) and segregation (i.e., clustering coefficient and local efficiency) in the right middle occipital gyrus and the left superior occipital gyrus (Batalle et al, 2012;Kartun-Giles and Bianconi, 2019).…”
Section: Discussionmentioning
confidence: 52%
“…We inferred that acupuncture stimulation affected these functional connections. Moreover, we also found that acupuncture stimulation affected functional interaction (i.e., degree) (Cecilia et al, 2018) and segregation (i.e., clustering coefficient and local efficiency) in the right middle occipital gyrus and the left superior occipital gyrus (Batalle et al, 2012;Kartun-Giles and Bianconi, 2019).…”
Section: Discussionmentioning
confidence: 52%
“…Apart from patients , the transitivity and reciprocity—when the first individual chooses the second individual, the second individual also chooses the first individual—of commenting user networks under other topics were higher than those of retweeting user networks. Consequently, compared to retweeting users, commenting users created a more cohesive community with the help of the commenting mechanism [ 75 ], and the relationship between users was close and relatively stable [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Apart from patients, the transitivity and reciprocity-when the first individual chooses the second individual, the second individual also chooses the first individual-of commenting user networks under other topics were higher than those of retweeting user networks. Consequently, compared to retweeting users, commenting users created a more cohesive community with the help of the commenting mechanism [75], and the relationship between users was close and relatively stable [76]. As shown in Figure 4, the retweeting and commenting user networks of rumor rebuttal under different topics showed highly modular structures; however, the large clusters in retweeting user networks showed high homophily, while the large clusters in commenting user networks had mixed attitudes.…”
Section: Echo Chamber Effect In User-level Interaction Networkmentioning
confidence: 99%
“…In this section, we will use TDA on our rsfMRI adjacency matrices. TDA can identify different characteristics of a network by addressing the high-order structure of a network beyond pair-wise connections as used in graph theory [30,51,52]. TDA generally uses topology and geometry methods to study the shape of the data [53].…”
Section: Topological Data Analysismentioning
confidence: 99%